2018
DOI: 10.3758/s13428-018-1099-3
|View full text |Cite
|
Sign up to set email alerts
|

The Glasgow Norms: Ratings of 5,500 words on nine scales

Abstract: The Glasgow Norms are a set of normative ratings for 5,553 English words on nine psycholinguistic dimensions: arousal, valence, dominance, concreteness, imageability, familiarity, age of acquisition, semantic size, and gender association. The Glasgow Norms are unique in several respects. First, the corpus itself is relatively large, while simultaneously providing norms across a substantial number of lexical dimensions. Second, for any given subset of words, the same participants provided ratings across all nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
234
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(241 citation statements)
references
References 59 publications
5
234
1
1
Order By: Relevance
“…This means that if variables from small corpora, or from multiple corpora with little overlap, are used as independent or control variables, the pool of possible stimuli will be greatly reduced. Similarly, variables are often highly correlated, for instance, as imageability and concreteness are (Scott et al, 2019). It would be Please Note: The final version of this manuscript has now been published with open access in peerreviewed journal, Behavior Research Methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that if variables from small corpora, or from multiple corpora with little overlap, are used as independent or control variables, the pool of possible stimuli will be greatly reduced. Similarly, variables are often highly correlated, for instance, as imageability and concreteness are (Scott et al, 2019). It would be Please Note: The final version of this manuscript has now been published with open access in peerreviewed journal, Behavior Research Methods.…”
Section: Discussionmentioning
confidence: 99%
“…An example box for specifying the levels of an independent variable in the Shiny app. Here, two levels (A1, A2) are being specified for the variable of Familiarity from the Glasgow Norms (Scott et al, 2019). In this case, the density plot shows that the distribution is skewed towards words rated as more familiar, with far fewer words rated as less familiar.…”
Section: The Shiny Appmentioning
confidence: 99%
“…We also included 160 pictures of natural landscapes (targets: n = 80; foils: n = 80), presented in the centre of the display (17 cm wide, 11 cm tall) that were i) not identifiable / known; ii) with no sign of manmade features (buildings, objects), or of people or animals. These images were taken from the royalty-free platform Shutterstock foils: U = 1653.50, p = 0.521) [see 49 for details on ratings of concreteness, imageability, familiarity, age of acquisition, arousal, and valence].…”
Section: Scenesmentioning
confidence: 99%
“…We used a total of 120 faces (Short Deadline Session: targets: n=30;foils:n=30; Long targets vs. foils: U = 220.5, p = 0.468) ; ix) mean ratings of arousal levels (targets: mean = 4.54, SD =1.05; foils: mean = 4.31; SD = 0.94; targets vs. foils: t = 0.77, p = 0.443); x) mean valence ratings (targets: M = 5.47, IQR = 1.04; foils: M = 5.49; IQR = 0.81; targets vs. foils: U = 242.0, p = 0.809) [see 49 for details on ratings of concreteness, imageability, familiarity, age of acquisition, arousal, and valence]. The same words were presented in the two sessions.…”
Section: Stimulus Materials Facesmentioning
confidence: 99%
“…The issue of multiple meanings and concreteness ratings was raised in the early 1980s (e.g., Gilhooly & Logie, 1980a;Toglia & Battig, 1978; see also Theijssen, van Halteren, Boves, & Oostijk, 2011), when research showed that at least 30% of words in English texts have multiple meanings (e.g., Britton, 1978). However, this idea never gained ground in concreteness-ratings studies (exceptions are Gilhooly & Logie, 1980b;Scott, Keitel, Becirspahic, Yao, & Serono, 2019;Wollen, Cox, Coahran, Shea, & Kirby, 1980). When different meanings of the same word refer to equally concrete (or abstract) entities, this may not affect the word's concreteness rating (Theijssen et al, 2011).…”
Section: Concreteness and Metaphoricitymentioning
confidence: 99%